The role of the principal-agent-client model in understanding corruption in the public procurement sector in Malaysia - Mohd Yusuf, Hairuzzaki; Mohd Yusof, Danial; Adnan, Normala (IIUM Press, 2024)
Corrupt practices in public procurement in Malaysia are explained in this paper using a principal-agent model. The government leaders, who are typically politicians, ministers, or their relatives, are referred to as the" principal" while the officials who carry out their duties are referred to as "agents". The actors in the model who constitute the third party — the other actor in the cycle of corruption — include clients, customers, and the public at large. The principal-agent-client framework was applied to 18 selected corruption cases in Malaysia to describe and analyse the actors involved in the transgressions and illegal acts in these cases. The cases were investigated by the Malaysian Anti-Corruption Commission (MACC) from 2014 to 2019, charged and found guilty by the courts in Malaysia. The findings show that all the actors in the role of agent were public officials, while the actors in the role of client were from the private sector, and the actors in the role of principal were high-ranking government officials, their relatives, and politicians.